FAKTOR-FAKTOR YANG MEMENGARUHI KEBERHASILAN REDENOMINASI - Nur Siti Annazah; Bambang Juanda; Sri Mulatsih (IPB University, 2017)
Redenomination is a simplification of the nominal value of the currency by reducing digits (zeros) without reducing the real value of the currency. The research was done because of the theoretical and empirical results are still a debate about the impact of redenomination policy on the economic perspective. This is due to the redenomination policy in each country has a different effect depending on economic conditions when redenomination is applied. The purpose of this study was to analyze the factors that influence the success of the redenomination of a country. Data used in the form of secondary data, historical data of 32 countries that have conducted redenomination. The analysis used is multiple regression. The results showed the better the condition of economic growth when redenomination is applied, it will lower inflation one year after the redenomination. Keywords: Economic growth, Inflation, Redenomination, Regression